Potential of Propolis for Diabetic Wound Healing: A Literature Review - Sukmana, Mayusef; Rasyid, Muhammad; Paramita, Swandari; Yasir, Yadi; Wahyuningsih, Sri (Griya Eka Sejahtera, 2025)
Background: Diabetes mellitus, a chronic metabolic disorder often leads to impaired wound healing, a serious complication resulting in diabetic ulcers, infections and even amputations. Conventional treatments for diabetic wounds can be costly and have side effects. Propolis, a natural resinous substance collected by honeybees from various plants, has long been recognized for including antibacterial, anti-inflammatory, antioxidant, and immunomodulatory properties. This literature review aims to summarize and analysed the scientific evidence regarding the potential of propolis in accelerating wound healing in diabetic conditions.Methods: Google Scholar, PubMed, Science Direct, EBSCO, Watase UAKE and Proquest using relevant keywords including